Taxonomic notes on the status of Syzygium caryophyllatum var. abrahamianum (Myrtaceae) - Shareef, S M; Santhosh Kumar, E S (Plant Science Today, 2026)
Syzygium caryophyllatum var. abrahamianum Shareef & E.S.S. Kumar is elevated to specific rank.